High‐resolution upper Pliocene to Pleistocene calcareous nannofossil biostratigraphy in Ocean Drilling Program Hole 1146A in the South China Sea. (2nd June 2021) - Emanuel, Sara; Sato, Tokiyuki; Chiyonobu, Shun; Shyu, J. Bruce H.; Bassi, Davide; Iryu, Yasufumi
Abstract: We established a high‐resolution calcareous nannofossil biostratigraphy for the late Pliocene–Pleistocene by analyzing a 242 m‐thick, continuous sedimentary succession from Ocean Drilling Program Site 1146, Hole A, in the South China Sea (SCS). A total of 14 calcareous nannofossil datums were detected in the SCS succession. They are, in descending order: first occurrence (FO) of Emiliania huxleyi, last occurrence (LO) of Pseudoemiliania lacunosa, LO of Reticulofenestra asanoi, FO of Gephyrocapsa parallela, FO of R. asanoi, LO of large Gephyrocapsa spp., FO of large G . spp., FO of Gephyrocapsa oceanica, FO of Gephyrocapsa caribbeanica, LO of Calcidiscus macintyrei, LO of Discoaster brouweri, LO of Discoaster pentaradiatus, LO of Discoaster surculus, and LO of Discoaster tamalis . The FO of E. huxleyi was not precisely detected due to poor preservation and dissolution of nannofossils in the underlying strata. We refined the previous calcareous nannofossil biostratigraphy in the SCS by identifying Gephyrocapsa species and four evolutionary extinction events of the genus Discoaster . The proposed calcareous nannofossil biostratigraphy correlates with those reported in other terrestrial and marine areas/sites and global benthic foraminiferal δ 18 O records. The age–depth curves based on nannofossil biostratigraphy indicate a significant increase in the sedimentation rates at the LO of R. asanoi (0.91–0.85 Ma). The timing of this increase corresponds to reef expansion in the Ryukyu Islands linked to a stepwise increase in Kuroshio Current intensity. This timing is broadly coeval with a sea surface temperature increase of ∼2 °C in the northwestern Pacific due to expansion of the Western Pacific Warm Pool towards the north and south subtropical regions. This can be explained by increased weathering and erosion of terrestrial areas in glacial periods and increased rainfall causing higher sediment transport in interglacial periods, which were both linked to Middle Pleistocene Transition‐related climatic changes.